Comparing the Efficacy of Visual Action Therapy Versus Auditory Comprehension Therapy in Individuals with Wernicke’s Aphasia - Ijaz, Zainab; Shahzadi, Shazia; Juhary, Ali; Munir, Naureen (2024)
The aims to investigate the comparative effectiveness of Visual Action Therapy (VAT) and Auditory Comprehension Therapy in individuals with Wernicke’s aphasia, a language impairment typically resulting from brain injury, often due to stroke. Wernicke’s aphasia manifests primarily as difficulty in understanding spoken language and reduced sentence length, while spoken word production remains relatively intact. Its prevalence is notably high among older individuals, particularly those aged 85 and above. This Randomized Control Trial (RCT) involved 12 participants divided equally into experimental and control groups. Over a three-month period, both groups underwent therapy sessions conducted at home, with the experimental group receiving VAT and the control group undergoing auditory training therapy. Each group participated in 10 weekly sessions lasting 30 minutes each. Analysis using SPSS version 21 indicated that VAT significantly enhanced comprehension skills in the experimental group compared to auditory comprehension therapy. Specifically, improvements were noted in speech production, word finding abilities, following sequential commands, auditory verbal fluency, repetition skills, and graphic reading. These findings underscore the efficacy of VAT in augmenting communication and aphasia screening scores among individuals with Wernicke’s aphasia. In conclusion, the study emphasizes the importance of understanding and implementing VAT techniques in clinical practice for managing Wernicke’s aphasia effectively. Continued knowledge and application of VAT approaches are crucial for optimizing therapeutic outcomes in this population.